Rattling spears : a history of Indigenous Australian art - McLean, Ian, 1952- (Reaktion Books, 2018)
Art of Indigenous peoples. Australian. Large, bold and colourful, Indigenous Australian art has impressed itself on the contemporary imagination. But it is controversial, dividing the stakeholders from those who smell a scam. Whether the artists are victims or victors, there is no denying their impact in the media and on the art world and collectors worldwide. How did it become the most successful Indigenous art in the world? How did its artists escape the ethnographic and souvenir markets to become players in an art world from which they had been barred? Superbly illustrated, this full historical account makes you question everything you were taught about modern and contemporary art.